The Attitudes towards the Euro : An Empirical Study based on the German Socio-Economic Panel (SOEP) - Thorsten Schneider; Bettina Isengard (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper investigates the attitudes towards the Euro and their changes over time in Germany by using longitudinal micro data from the German Socio Economic Panel Study (SOEP). We observe that a large part of the German population was worried about the new currency before its implementation. Individual changes of worries can be explained by theories of selfperception and cognitive dissonance. According to these theories, concerns should diminish after the Euro notes and coins are distributed. In contrast, the theory of reactance predicts an increase, while the theories of attitude changes as learning processes offer both its increase and decrease. The latter seems to be the most suitable explanation for the development of concerns about the Euro. We discover that problems with the handling of the new money and the time of questioning are strong predictors. The time pattern goes hand in hand with the time of press coverage on price rises. As worries are connected with problems in handling the new money, future member states of the European Monetary Union should prepare their population in a better manner than the existing member states did.
Keywords: A14; E49; D83; 330; Euro; European Union; Attitudes; Changes of Attitudes; National Identity; Euro; Währungsumstellung; Meinung; Deutschland